2020
DOI: 10.3390/rs12213563
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Precursors in VLF Subionospheric Signals Related to Strong Earthquakes (M > 7) in Western China and Possible Explanations

Abstract: Earthquakes may disturb the lower ionosphere through various coupling mechanisms during their seismogenic and coseismic periods. The VLF signal radiated from ground-based transmitters is affected when it passes near the disturbed region above the seismogenic area, and this anomaly can be recorded by ground-based VLF receivers. In this paper, the seismic anomalies before two strong earthquakes (M>7) that occurred in western China were detected using the ground-based observation of VLF signal; the possible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…These anomalies were observed for EQs with magnitude more than 5.5, shallow depth up to 32 km, and epicenter position less than 185 km off the TRGCP. Our results are consistent with the earlier results of Hayakawa et al (2011), Kasahara et al (2010) and Khadka et al (2017) who found a simultaneous decrease in the T and increase in the NF and D. The T showed a decrease in the average of nighttime dA(t) values on EQ day because of the reduction in the ionospheric VLF reference height (Molchanov et al, 1998;Zhao et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…These anomalies were observed for EQs with magnitude more than 5.5, shallow depth up to 32 km, and epicenter position less than 185 km off the TRGCP. Our results are consistent with the earlier results of Hayakawa et al (2011), Kasahara et al (2010) and Khadka et al (2017) who found a simultaneous decrease in the T and increase in the NF and D. The T showed a decrease in the average of nighttime dA(t) values on EQ day because of the reduction in the ionospheric VLF reference height (Molchanov et al, 1998;Zhao et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Studies of the ionospheric changes as precursors of earthquakes report changes usually a few days before events [9,13,35]. These lower ionosphere disturbances are detected as the solar terminator shift [13,36,37] and deviations of the time evolutions of signal characteristics from values recorded during days with unperturbed conditions [5,38] (in time domain), and as variations in the wavelet power spectrum [5,39] (in frequency domain), and all of these changes are shown for both signal amplitude and phase. The recent analysis presented in [33] shows reduction of the amplitude noise of the VLF signal less than one hour before the earthquake occurred near Kraljevo, Serbia, on 3 November 2010 (the seismotectonic model of this event is presented in [40]), as well as excitation and attenuation of the acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [73], seismic anomalies before two strong earthquakes with M w > 7 in western China were detected using ground-based observation of VLF signals from monitoring stations. A full wave model was used to research possible factors inducing seismic anomalies on the received VLF electric field.…”
Section: Electromagnetic Radiationmentioning
confidence: 99%